China’s Fading Twin Surpluses and Its Policy Implications (Journal of International Studies, 2014)
This paper argues that the twin surpluses of China's balance of payment tend to vanish in the future due to some external and internal structural changes. China's current account surplus would diminish due to the decline of good trade surplus and the expanding service trade deficit and negative investment income. China’s capital account surplus might turn into deficit as a result of shrinking net direct investment income and rising volatile short-term capital flows. The fading twin surpluses would speed up the normalization of US treasury bond yields, terminate the one way appreciation of RMB exchange rate, alleviate PBC's sterilization pressure as well as cause new problem for PBC, and pose new financial vulnerability to Chinese economy. Finally, this paper provides some policy suggestions to deal with the new challenges brought by the shrinking twin surpluses.